The Federalist A Classic on Federalism and Free Government - Dietze, Gottfried (Johns Hopkins University Press, 2019)
Originally published in 1960. The Federalist-a treatise on free government in peace and security-is one of the most important contributions to the literature on constitutional democracy and federalism in the United States. Scholars, lawyers, judges, and statesmen in the United States and abroad have lauded the impact of The Federalist. John Quincy Adams referred to the papers as a "classical work in the English language, and a commentary on the Constitution of the United States, of scarcely less authority than the Constitution itself." Since the publication of the papers, historians have analyzed the collected work from a variety of approaches, but at the time that Gottfried Dietze wrote in 1960, scholars mainly concentrated on specific components of The Federalist. Dietze intervened in this scholarship by offering a comprehensive study of the work, which promoted federalism as both a means for establishing free government and securing peace within a federal state and for maintaining security under the threat of foreign powers. In addition to a theoretical examination of the text, Dietze brings in a historical component by fleshing out how its authors were shaped by the political atmosphere in which they lived and how their writings transformed political literature for generations to come